A framework for mapping and monitoring human-ocean interactions in near real-time during COVID-19 and beyond. (June 2022) - Ward-Paige, CA; White, ER; Madin, EMP; Osgood, GJ; Bailes, LK; Bateman, RL; Belonje, E.; Burns, KV; Cullain, N.; Darbyshire-Jenkins, P.; de Waegh, R.S.; Eger, AM; et al.
Abstract: The human response to the COVID-19 pandemic set in motion an unprecedented shift in human activity with unknown long-term effects. The impacts in marine systems are expected to be highly dynamic at local and global scales. However, in comparison to terrestrial ecosystems, we are not well-prepared to document these changes in marine and coastal environments. The problems are two-fold: 1) manual and siloed data collection and processing, and 2) reliance on marine professionals for observation and analysis. These problems are relevant beyond the pandemic and are a barrier to understanding rapidly evolving blue economies, the impacts of climate change, and the many other changes our modern-day oceans are undergoing. The "Our Ocean in COVID-19″ project, which aims to track human-ocean interactions throughout the pandemic, uses the new eOceans platform (eOceans.app) to overcome these barriers. Working at local scales, a global network of ocean scientists and citizen scientists are collaborating to monitor the ocean in near real-time. The purpose of this paper is to bring this project to the attention of the marine conservation community, researchers, and the public wanting to track changes in their area. As our team continues to grow, this project will provide important baselines and temporal patterns for ocean conservation, policy, and innovation as society transitions towards a new normal. It may also provide a proof-of-concept for real-time, collaborative ocean monitoring that breaks down silos between academia, government, and at-sea stakeholders to create a stronger and more democratic blue economy with communities more resilient to ocean and global change.